My life is murder. [Series 1] [videorecording (DVD)] - Purcell, Leah, 1970-; King, Mat, 1975-; Lawless, Lucy, 1968-; Curry, Bernard; Vagulans, Ebony (Acorn Media, 2020)
Follows retired detective, Alexa Crowe, as she helps her former colleague solve crimes with the help of a young police data analyst.